2019
DOI: 10.14202/vetworld.2019.1472-1477
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathological immunohistochemical study of low pathogenic avian influenza virus H5N1 infection in lovebirds (Agapornis spp.) in Indonesia

Abstract: Background and Aim:To date, persistent infection with low pathogenic avian influenza virus (AIV) subtype H5N1 (LPAI H5N1) in chickens is widespread in Indonesia. Commercially available ornamental birds on markets play an important role in triggering the occurrence of AIV outbreaks. Thus, the presence of AIV in ornamental birds such as lovebirds needs to be closely monitored. Here, the presence of LPAI H5N1 was investigated in lovebirds with no clinical signs that, although apparently healthy, can be a continuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
2
0
0
Order By: Relevance
“…Pneumonic areas with intense aggregation of leukocytes and vasculitis of the pulmonary blood vessels were also detected in lung. These present histopathological findings are consistent with several previous pathological data reported with HPAI in the literature [ 42 , 44 , 48 , 51 , 52 , 53 ]. In these previous studies [ 42 , 44 , 48 , 51 , 52 , 53 ], trachea and lungs showed congestion, edema, thrombosis, diffuse hemorrhages, necrosis, and sloughing of the epithelial lining of trachea and bronchi, extensive alveolar damage, together with inflammatory cells infiltration including macrophages, lymphocytes, and heterophils.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Pneumonic areas with intense aggregation of leukocytes and vasculitis of the pulmonary blood vessels were also detected in lung. These present histopathological findings are consistent with several previous pathological data reported with HPAI in the literature [ 42 , 44 , 48 , 51 , 52 , 53 ]. In these previous studies [ 42 , 44 , 48 , 51 , 52 , 53 ], trachea and lungs showed congestion, edema, thrombosis, diffuse hemorrhages, necrosis, and sloughing of the epithelial lining of trachea and bronchi, extensive alveolar damage, together with inflammatory cells infiltration including macrophages, lymphocytes, and heterophils.…”
Section: Discussionsupporting
confidence: 93%
“…These present histopathological findings are consistent with several previous pathological data reported with HPAI in the literature [ 42 , 44 , 48 , 51 , 52 , 53 ]. In these previous studies [ 42 , 44 , 48 , 51 , 52 , 53 ], trachea and lungs showed congestion, edema, thrombosis, diffuse hemorrhages, necrosis, and sloughing of the epithelial lining of trachea and bronchi, extensive alveolar damage, together with inflammatory cells infiltration including macrophages, lymphocytes, and heterophils. In addition, depletion of the lymphoid follicles and heterophilic cells infiltration was observed in the spleen, together with hemorrhagic foci and necrosis of the periellipsoid lymphocyte sheaths, which is consistent with several previous studies [ 43 , 48 , 51 ].…”
Section: Discussionsupporting
confidence: 93%